Calcitonin gene‐related peptide (CGRP): A novel target for Alzheimer's disease. (17th April 2017) - Singh, Yogendra; Gupta, Gaurav; Shrivastava, Birendra; Dahiya, Rajiv; Tiwari, Juhi; Ashwathanarayana, Madhu; Sharma, Rakesh Kumar; Agrawal, Mohit; Mishra, Anurag; Dua, Kamal
Summary: Alzheimer's disease (AD) is leading cause of death among older characterized by neurofibrillary tangles, oxidative stress, progressive neuronal deficits, and increased levels of amyloid‐ β (A β ) peptides. Cholinergic treatment could be the best suitable physiological therapy for AD. Calcitonin gene‐related peptide (CGRP) is a thirty‐seven‐amino acid regulatory neuropeptide resulting from different merging of the CGRP gene, which also includes adrenomedullin, amylin, calcitonin, intermedin, and calcitonin receptor‐stimulating peptide. It is a proof for a CGRP receptor within nucleus accumbens of brain that is different from either the CGRP1 or CGRP2 receptor in which it demonstrates similar high‐affinity binding for salmon calcitonin, CGRP, and amylin, a possession which is not shared by any extra CGRP receptors. Binding of CGRP to its receptor increases activated cAMP‐dependent pkA and PI3 kinase, resulting in N‐terminal fragments that are shown to exert complex inhibitory as well facilitator actions on nAChRs. Fragments such as CGRP1‐4, CGRP1‐5, and CGRP1‐6 rapidly as well as reversibly improve agonist sensitivity of nAChRs without straight stimulating those receptors and produce the Ca 2+ ‐induced intracellular Ca 2+ mobilization. Renin–angiotensin–aldosterone system (RAAS)‐activated angiotensin‐type (AT4) receptor is also beneficial in AD. It has been suggested that exogenous administration of CGRP inhibits infiltration of macrophages and expression of various inflammatory mediators such as NFkB, IL‐1b, TNF‐ α, iNOS, matrix metalloproteinase (MMP)‐9, and cell adhesion molecules like intercellular adhesion molecule (ICAM)‐1 which attenuates consequence of inflammation in AD. Donepezil, a ChEI, inhibits acetylcholinesterase and produces angiogenesis and neurogenesis, in the dentate gyrus of the hippocampus of WT mice after donepezil administration. However, none of the results discovered in CGRP‐knockout mice and WT mice exposed to practical denervation. Therefore, selective agonists of CGRP receptors may become the potential candidates for treatment of AD.